Strategi Pengembangan Objek Wisata Pemandian Aek Parsariran Di Kecamatan Batang Toru Kabupaten Tapanuli Selatan Tahun 2023 - Fransiska Rambe; Robert Juni Tua Sitio; Rusmauli Simbolon; Yulia K S Sitepu; Tio R J Nadeak (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to determine the strategy for developing the Aek Parsariran bathing tourist attraction and the supporting and inhibiting factors for developing the Aek Parsariran bathing tourist attraction. This research uses qualitative research methods with a descriptive approach and data collection techniques through observation, documentation and interviews with eleven informants. The results of this research describe that the government has a strategy in developing the Aek Parsariran Baths tourist attraction through four main programs, namely: Completing Attractions, Improving Facilities, Creating Prohibition Holes, Providing Services.